2006
DOI: 10.1080/08923970600626007
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Anti-Inflammatory Activities of the PlantAndrographis PaniculataNees

Abstract: In this study, we explored the antioxidant and anti-inflammatory properties of the medicinal herb Andrographis paniculata using in vitro as well as in vivo systems. Methanolic extract of Andrographis paniculata was found to inhibit formation of oxygen derived free radicals such as superoxide (32%) hydroxyl radicals (80%) lipid peroxidation (80%) and nitric oxide (42.8%) in in vitro system. In vivo studies using BALB/c mice models also showed significant inhibition in PMA induced superoxide (32.4%) and nitric o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
80
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(82 citation statements)
references
References 29 publications
2
80
0
Order By: Relevance
“…68) An anti-inflammatory benefit of andrographolide by reduction of inducible nitric oxide synthase (iNOS) protein expression through prevention of the de novo protein synthesis and decreasing the protein stability via a post-transcriptional mechanism has been inferred. [7][8][9] Furthermore, andrographolide exerted anti-inflammatory effects by inhibiting nuclear factor (NF)-κB binding to DNA, and thus reducing the expression of proinflammatory proteins, such as cyclooxygenase-2 (COX-2). 69) Another study showed weak antiinflammatory effects of andrographolide compared to other diterpenoid constituents in the plant, 4) in which the anti-inflammatory effect probably worked by a mechanism that involves secreted material from adrenal glands, since such effects disappeared in adrenalectomized animals.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…68) An anti-inflammatory benefit of andrographolide by reduction of inducible nitric oxide synthase (iNOS) protein expression through prevention of the de novo protein synthesis and decreasing the protein stability via a post-transcriptional mechanism has been inferred. [7][8][9] Furthermore, andrographolide exerted anti-inflammatory effects by inhibiting nuclear factor (NF)-κB binding to DNA, and thus reducing the expression of proinflammatory proteins, such as cyclooxygenase-2 (COX-2). 69) Another study showed weak antiinflammatory effects of andrographolide compared to other diterpenoid constituents in the plant, 4) in which the anti-inflammatory effect probably worked by a mechanism that involves secreted material from adrenal glands, since such effects disappeared in adrenalectomized animals.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…5) In Thailand, this plant was selected by the Ministry of Public Health as one of the medicinal plants to be included in "The National List of Essential Drugs A.D. 1999" (List of Herbal Medicinal Products). 6) Extensive research has revealed that Andrographis paniculata has a surprisingly broad range of pharmacological effects and some of them are extremely beneficial, such as antiinflammatory, [7][8][9][10][11] antidiarrhoeal, 12,13) antiviral, 14) anti-malarial, 15,16) hepatoprotective, [17][18][19][20][21][22][23][24][25][26][27][28][29] cardiovascular, 30,31) anticancer, [32][33][34][35][36][37][38][39] and immunostimulatory [40][41][42][43][44] activities. On the other hand, male reproductive toxicity 45) and cytotoxicity 46) of this plant have been reported as well.…”
Section: Introductionmentioning
confidence: 99%
“…9 Andrographolide (AG; Figure 1) is a natural diterpenoid isolated from Andrographis paniculata, which is a traditional remedy for fever, cold, sore throat, and various chronic infectious diseases. [10][11][12] Moreover, previous studies have shown that AG possesses many pharmacological activities, including anti-inflammatory, 13 antioxidative, 14 and anticancer 15 activities. A previous study showed that pretreatment with the ethanolic extract of A. paniculata provided significant protection against gastric ulcers.…”
Section: Introductionmentioning
confidence: 99%
“…However, following intraperitoneal administration of andrographolide (4 mg/kg) significant reduction in paw volume was observed (Suebsasana et al, 2009); following subcutaneous administration (10, 25 and 50 mg/kg) dose dependent anti-inflammatory effect was observed (Sulaiman et al, 2010); following intraperitoneal administration of andrographolide sulfonic acid sodium salt in high (88 mg/kg) or low (22 mg/kg) doses significant reduction in rat paw swelling caused by the egg white was observed (Wen et al, 2014) and following intraperitoneal administration of Andrographis paniculata extract (methanolic) for 5 consecutive days (10 mg/dose/animal) was found to inhibit carrageenan induced paw oedema formation compared to untreated controls group (Sheeja et al, 2006). No anti-inflammatory effect in rats may be due to poor solubility of pure andrographolide, difference in vehicle used for administration and effective plasma concentration may be high.…”
Section: % Inhibition In Paw Oedema After Drug Administrationmentioning
confidence: 99%